Exemplars to Excellence: Teachers’ Perspectives on the Role of Lesson Exemplars in Instructional Delivery within the Revised K–12 Curriculum - Anselmo, Charlie T.; Andres, Jumat T.; Estabillo, Sannyval R.; Galasi, Aljhun G.; Lappay, Jasmin I. (Future Science / FSH-PH Publications, 2025)
This study examined the perspectives of Senior High School teachers regarding the utilization of lesson exemplars in instructional delivery within the Revised K-12 Curriculum. Utilizing a descriptive-evaluative survey design, data were gathered from 25 purposively selected teachers through the use of structured questionnaires. The findings indicate that teachers perceive lesson exemplars as well-structured, logically sequenced, and closely aligned with the Most Essential Learning Competencies (MELCs). They found the exemplars to be applicable and practical for classroom instruction, supporting various teaching methods and strategies. As early adopters of the enhanced curriculum, teachers acknowledged facing challenges such as limited training opportunities and the necessity of adapting exemplars to diverse contexts. No significant differences were observed in teachers' perceptions when categorized by sex, age, years of teaching experience, or strand handled. Thematic analysis identified areas for improvement, including managing time constraints, balancing activity load, and ensuring contextual alignment. Teachers recommended streamlining exemplar activities, providing supplementary resources, expanding professional development, and enriching exemplar content to enhance the impact of the training. The study concludes that lesson exemplars are highly effective tools for instructional delivery, and with ongoing refinement and robust institutional support, they can empower teachers to maximize student engagement, enhance instructional quality, and advance the objectives of the K-12 to curriculum. Recommendations include simplifying activities, providing adequate references and support materials, strengthening teacher preparation through professional development programs, and integrating higher-order thinking skills and concrete examples into the content of these programs.